ANALISIS KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDEX HIGH DIVIDEN 20 DI BURSA EFEK INDONESIA (BEI) - Muhammad Akbar, - (2021)
This research is a quantitative study which aims to show the effect of institutional ownership, liquidity, leverage, growth, and free cash flow on dividend policy. This study uses an object, namely the high dividend index of 20 which is listed on the Indonesia Stock Exchange in the 2017-2019 period. The sample of this research is 20 companies during the 2017-2019 period. Hypothesis testing in this study uses Multiple Linear Regression Analysis with the Eviews 9.0 program and a significance level of 5% (0.05). The results of the test obtained (1) there is no significant effect of institutional ownership on dividend policy, (2) there is no significant effect of liquidity on dividend policy (3) there is a negative effect on dividend policy, (4) there is no significant effect of growth on dividend policy , (5) there is a positive and insignificant effect of free cash flow on dividend policy.